Stochastic modeling of the c.acetobutylicum and solvent productions in fermentation [electronic resource] - Mohd. Khairul Bazli Mohd. Aziz, 1985- (2010)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2010